A poro-damage phase field model for hydrofracturing of glacier crevasses. (May 2021) - Sun, Xiangming; Duddu, Ravindra; Hirshikesh,
Abstract: Hydraulic fracture (or hydrofracture) can promote the propagation of meltwater-filled surface crevasses in glaciers and, in some cases, lead to full-depth penetration that can enhance basal sliding and iceberg calving. Here, we propose a novel poro-damage phase field model for hydrofracturing of glacier crevasses, wherein the crevasse is represented by a nonlocal damage zone and the effect of hydrostatic pressure due to surface meltwater is incorporated based on Biot's poroelasticity theory. We find that the elastic strain energy decomposition scheme of Lo et al. (2019) with an appropriate fracture energy threshold can adequately represent the asymmetric tensile–compressive fracture behavior of glacier ice subjected to self-gravity loading. We assessed the performance of the model against analytical linear elastic fracture mechanics solutions by comparing their predictions of maximum crevasse penetration depth. The model simulates both surface crevasse propagation in the interior region of the glacier, as well as cliff failure in the terminus region. The excellent performance of the proposed model for air/water-filled surface crevasses in idealized land- and marine-terminating grounded glaciers illustrates its applicability to studying the dynamic response of glaciers to atmospheric warming.